Mechanical Behavior of High-Strength Low-Alloy Steels - Filippo Berto (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
High-strength low-alloy steels are designed to provide specific desirable combinations of properties, such as strength, toughness, formability, weldability, and corrosion resistance. These features make them ideal for critical applications under severe service conditions and in aggressive environments, namely rail and road vehicles, passenger car components, construction machinery, industrial equipment, offshore structures, gas pipelines, and bridges, among others. This Special Issue aims to address the mechanical behavior of high-strength low-alloy steels from different perspectives, namely in terms of mechanical deformation, damage, and failure. It gathers scientific contributions from authors working in various fields, for instance processing techniques, the modeling of the mechanical behavior, the characterization of material microstructure, the influence of environmental parameters, temperature dependence, as well as advanced applications.